EVALUATING THE IMPLEMENTATION OF PEOPLE AND PLANET CORPORATE SOCIAL RESPONSIBILITY PROGRAM OF PT TIRTA INVESTAMA USING IMPORTANCE PERFORMANCE ANALYSIS - Mawei, Priskila Firsty; Kindangen, Paulus; Pandowo, Merinda (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Function of a company not only to increase profit but also responsible to the environment and society where the company located. This activity called Corporate Social Responsibility. CSR means that a corporation should act in a way that enhances society and be held accountable for any actions that affect people, their communities, and their environment. The objectives of this research is to evaluate importance and performance of the implementation of CSR program based on people and planet program at PT. Tirta Investama. method of the research is using importance performance analysis. The population observed all people who lives in Airmadidi Bawah, with sample size as many as 100 respondents and sampled using purposive sampling. The result showed that waste management, water access, education and health facilities, environmental conservation, and communication are attributes that very important and also the performance of the company is high, while the other attribute there is a very important but low performance, then not important but performance is high, and last there is attribute located in unimportant and low performance. From the results of this research, the researchers suggest PT Tirta Investama to pay attention and improve the attributes that have low performance and maintain programs that has high performance to get better.Â Keywords: corporate social responsibility, people and planet, importance and performance analysis